Hip replacement. Issue 10158 (3rd November 2018) - Ferguson, Rory J; Palmer, Antony JR; Taylor, Adrian; Porter, Martyn L; Malchau, Henrik; Glyn-Jones, Sion
Summary: Total hip replacement is a frequently done and highly successful surgical intervention. The procedure is undertaken to relieve pain and improve function in individuals with advanced arthritis of the hip joint. Symptomatic osteoarthritis is the most common indication for surgery. In paper 1 of this Series, we focus on how patient factors should inform the surgical decision-making process. Substantial demands are placed upon modern implants, because patients expect to remain active for longer. We discuss the advances made in implant performance and the developments in perioperative practice that have reduced complications. Assessment of surgery outcomes should include patient-reported outcome measures and implant survival rates that are based on data from joint replacement registries. The high-profile failure of some widely used metal-on-metal prostheses has shown the shortcomings of the existing regulatory framework. We consider how proposed changes to the regulatory framework could influence safety.